LIMB LENGTH DISCREPANCY IN LOWER LIMB MANAGEMENT WITH UNILATERAL EXTERNAL FIXATOR - Hussain, Shahid; Inam, Muhammad; Arif, Muhammad; Shabbir, Muhammad; Ahmad, Israr (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the outcome of lower limb lengthening with unilateral external fixator in limb length discrepancy. Material and Methods: This descriptive study was conducted at the Department of Orthopedics Postgraduate Medical Institute, Hayatabad Medical Complex, Peshawar from 2002 to 2005, on 35 patients treated by Wagner method for their limb-length discrepancy. The limb-length discrepancy and bony alignment was measured and ascertained both clinically and radiologically. Unilateral external fixator assembly was fixed on the affected limb, percutaneous corticotomy was carried out and distraction was started one millimeter per day after one week. Distraction gap was assessed and measured with periodic radiological examination. Results: Out of 35 patients, 25 were male and 10 were females. Their ages ranged from 18 years to 50 years with a mean of 29.3 years. In 17 (48.6%) patients tibial lengthening, in 14 (40%) patients femoral lengthening and 4 (11.4%) patients both tibial and femoral lengthening was done. A total of 207 complications occurred in 39 segments. Out of which 128 were minor and 79 were major complications. We were able to achieve excellent or good grade in 89% of bony results and 97% of functional results, as per criteria of the association for the study and application of the Wagner method. Conclusion: The outcome of Wagner method for limb lengthening is excellent in over 80% of cases both in terms of bony and functional results.